2014
DOI: 10.1063/1.4890659
|View full text |Cite
|
Sign up to set email alerts
|

Asymmetric recombination and electron spin relaxation in the semiclassical theory of radical pair reactions

Abstract: We describe how the semiclassical theory of radical pair recombination reactions recently introduced by two of us [D. E. Manolopoulos and P. J. Hore, J. Chem. Phys. 139, 124106 (2013)] can be generalised to allow for different singlet and triplet recombination rates. This is a non-trivial generalisation because when the recombination rates are different the recombination process is dynamically coupled to the coherent electron spin dynamics of the radical pair. Furthermore, because the recombination operator is… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
47
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
3
1

Relationship

4
6

Authors

Journals

citations
Cited by 40 publications
(47 citation statements)
references
References 29 publications
0
47
0
Order By: Relevance
“…It seems likely that the lower the overall anisotropy of the radical pair, the less scope there would be for J-modulation to relax the spins anisotropically. Unfortunately it is difficult to explore this without much more efficient techniques for simulating large spin systems [61,62]. Extending this line of argument, we speculate that the enhancement arising from J-modulation is more likely to be observed for a radical pair in which the + TrpH C • radical has been replaced by a radical with fewer, smaller, more isotropic hyperfine interactions (e.g.…”
Section: Relaxation-enhanced Compass Sensitivity In Cryptochromementioning
confidence: 70%
“…It seems likely that the lower the overall anisotropy of the radical pair, the less scope there would be for J-modulation to relax the spins anisotropically. Unfortunately it is difficult to explore this without much more efficient techniques for simulating large spin systems [61,62]. Extending this line of argument, we speculate that the enhancement arising from J-modulation is more likely to be observed for a radical pair in which the + TrpH C • radical has been replaced by a radical with fewer, smaller, more isotropic hyperfine interactions (e.g.…”
Section: Relaxation-enhanced Compass Sensitivity In Cryptochromementioning
confidence: 70%
“…In fact, the initial electronic singlet state of the radical pair is quantum mechanically entangled [although the entanglement, as such, confers no advantage in terms of the general operation of the compass (60), nor is it essential for the existence of the spike]. We recently showed that the spin dynamics of long-lived radical pairs in weak magnetic fields can be described by a semiclassical approximation that becomes increasingly accurate as the number of nuclear spins is increased (61,62). If the behavior of a realistic radical pair magnetoreceptor can be satisfactorily modeled in terms of classical rather than quantum oscillations, then arguably it does not belong under the quantum biological umbrella.…”
Section: Discussionmentioning
confidence: 99%
“…It seems likely that the lower the overall anisotropy of the radical pair, the less scope there would be for J-modulation to relax the spins anisotropically. Unfortunately it is difficult to explore this without much more efficient techniques for simulating large spin systems [61,62].…”
Section: Relaxation-enhanced Compass Sensitivity In Cryptochromementioning
confidence: 99%